Machinery's handbook a reference book for the manufacturing and mechanical engineer, designer, drafter, metalworker, toolmaker, machinist, hobbyist, educator, and student - Oberg, Erik 1881-1951 (Industrial Press, 2020)
Since the first edition published more than 100 years ago, this handbook has been the most popular engineering resource of all time. Universally considered the principal reference in the manufacturing and mechanical industries, the Handbook is the ultimate collection of essential information needed by engineers, designers, drafters, metalworkers, toolmakers, machinists, educators, students, and serious home hobbyists. From engineering and design departments, machine and metalworking shops, and a wide range of manufacturing and industrial facilities, to countless classrooms and workshops worldwide, this is the must-have technical reference.